2021
DOI: 10.30699/ijp.2020.115747.2258
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Study of Patients with Primary Amenorrhea in the Northeast of Iran

Abstract: Background & Objective: Primary amenorrhea refers to the absence of menstruation in females of reproductive by age 16 when the development of secondary sexual characteristics is evident (breast development, pubic hair) or by age 14 when there are no secondary sexual characteristics are present. Primary amenorrhea can occur in several quite different reasons. Common hormonal causes of primary amenorrhea include constitutional delay, hypothalamic or pituitary disorders, chronic systemic disease, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…Short stature and delayed puberty, and lack of incidence of secondary sexual characteristics were significant clinical symptoms amongst these patients. This result was in line with previous studies, which reported that TS is the most commonly observed CA in PA, and also strengthened the role of the sex chromosome in the reproduction of females [17,25,28]. In this study, out of 30 cases of SA, two (6.6%) revealed a variety of CA.…”
Section: Discussionsupporting
confidence: 92%
“…Short stature and delayed puberty, and lack of incidence of secondary sexual characteristics were significant clinical symptoms amongst these patients. This result was in line with previous studies, which reported that TS is the most commonly observed CA in PA, and also strengthened the role of the sex chromosome in the reproduction of females [17,25,28]. In this study, out of 30 cases of SA, two (6.6%) revealed a variety of CA.…”
Section: Discussionsupporting
confidence: 92%
“…18 According to previous studies, primary amenorrhea due to chromosomal abnormalities was reported varied from 15.9% to 63.3% and turner syndrome either 45,X or its mosaic form is the leading cause of primary amenorrhea. 11 A comprehensive family history and physical examination and laboratory testing of affected individuals are required for diagnosis. The clinicians should inquire about the height, weight and body mass index of those with delayed puberty since they may present with short stature.…”
Section: Discussionmentioning
confidence: 99%
“…Primary amenorrhea (PA) is defined as lack of menarche or absence of menstruation in females of reproductive by age 16 when the development of secondary sexual characteristic is evident (breast development, pubic hair) or by age 14 when there are no secondary sexual characteristics are present. 11 PA is one of the most common reasons of obstetric-gynaecologic consultation in adolescent girls. The primary amenorrhea is categorized into functional or anatomic defect of hypothalamus, pituitary, uterus or ovaries, and genetic defect at chromosomal or molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Primary amenorrhea as the common symptom has a complicated etiology, and genetic disorders are non‐negligible. Copy number variants and abnormal structure of the X chromosome even XY karyotype have been reported in females with primary amenorrhea, showing that early cytogenetic is necessary for the evaluation of primary amenorrhea 1 . However, some genetic diseases could lead to primary amenorrhea caused by gonadal digenesis or hypogonadism, such as congenital adrenal hyperplasia (CAH), 2 Kallmann syndrome (KS), 3 Swyer syndrome, 4 Frasier syndrome, and so on 5 …”
Section: Introductionmentioning
confidence: 99%
“…Copy number variants and abnormal structure of the X chromosome even XY karyotype have been reported in females with primary amenorrhea, showing that early cytogenetic is necessary for the evaluation of primary amenorrhea. 1 However, some genetic diseases could lead to primary amenorrhea caused by gonadal digenesis or hypogonadism, such as congenital adrenal hyperplasia (CAH), 2 Kallmann syndrome (KS), 3 Swyer syndrome, 4 Frasier syndrome, and so on. 5 KS (OMIM 308700) is a rare inherited disease characterized by the combination of isolated hypogonadotropic hypogonadism (IHH) and anosmia.…”
Section: Introductionmentioning
confidence: 99%